2003
DOI: 10.1097/00005537-200308000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing Function and Tracheotomy Dependence After Combined‐Modality Treatment Including Free Tissue Transfer for Advanced‐Stage Oropharyngeal Cancer

Abstract: Combined-modality treatment that includes free flap reconstruction for advanced-stage oropharyngeal cancer may provide reasonable functional rehabilitation with respect to postoperative airway and swallowing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
40
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 16 publications
4
40
0
Order By: Relevance
“…Previous studies have reported reasonable functional outcomes following regional pedicled and microvascular free flap reconstruction of oropharyngeal defects, [15][16][17][18][19] although the extent of disease and previous treatment differed widely within and among studies. With regard to speech, over two thirds of patients attained >80% intelligibility in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported reasonable functional outcomes following regional pedicled and microvascular free flap reconstruction of oropharyngeal defects, [15][16][17][18][19] although the extent of disease and previous treatment differed widely within and among studies. With regard to speech, over two thirds of patients attained >80% intelligibility in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] There is an established school of thought that early postoperative oral feeding increases the potential for an orocutaneous fistula in these patients, and surgeons have traditionally adopted a conservative approach and kept patients "nil by mouth" for 6-12 days before oral feeding is resumed. 6 It has often been thought that early use of the tongue and pharynx after operation would place excessive stresses across the intraoral closure and lead to dehiscence of the flap and potentially to contamination of the neck and formation of an orocutaneous fistula. These views may have their origin in traditional practices adopted in general surgery after small bowel or colorectal resection and anastomosis, but since the 1990s, with the introduction of multimodal perioperative care with fasttrack surgery and improved recovery programmes, ideas on delayed function have changed.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a tracheotomy is associated with a significant deterioration in quality of life. 26 Silent and undetected aspirations, which can impact on the lung, 21 tended to be more frequent in the non-surgical group: 67% vs. 50% (non-significant). This can be explained by the loss of sensitivity resulting from oedema and post-radiation fibrosis, but may also be neurogenic.…”
Section: Discussionmentioning
confidence: 89%